2005
DOI: 10.1292/jvms.67.659
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Selective Phosphodiesterase Inhibitors on Carbachol-Induced Contraction and Cyclic Nucleotide Contents in the Guinea Pig Gall Bladder

Abstract: ABSTRACT. The effects of various selective phosphodiesterase (PDE) inhibitors on muscle contractility and cyclic nucleotide contents in the guinea pig gall bladder were investigated. Various selective PDE inhibitors, vinpocetine (type 1), erythro-9-(2-hydroxy-3-nonyl)adenine (EHNA, type 2), milrinone (type 3), Ro20-1724 (type 4), and zaprinast (type 5), inhibited CCh-induced contractions in a concentration-dependent manner. The rank order of potency for the gall bladder was Ro20-1724 > vinpocetine > EHNA >milr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…It has been reported that rolipram (type 4) potently relaxed electrical field stimulation-induced contraction in the cat gastric fundus [1]. Ro20-1724 inhibited CCh-induced contraction in the bovine abomasum (in the present study) and guinea pig gall bladder [14] potently, but poorly in the guinea pig ileum [12] and taenia coli [13]. These data suggested that the functional distributions of PDE4 isozymes of gastrointestinal smooth muscles differ by organ.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…It has been reported that rolipram (type 4) potently relaxed electrical field stimulation-induced contraction in the cat gastric fundus [1]. Ro20-1724 inhibited CCh-induced contraction in the bovine abomasum (in the present study) and guinea pig gall bladder [14] potently, but poorly in the guinea pig ileum [12] and taenia coli [13]. These data suggested that the functional distributions of PDE4 isozymes of gastrointestinal smooth muscles differ by organ.…”
Section: Discussionsupporting
confidence: 49%
“…Moreover, the PDE1-5 isozymes have selective inhibitors [5], and selective inhibitors for PDE7 and 9 have also been made recently and commercialized. It has been shown that the potency of the relaxation induced by these PDE inhibitors differed in many smooth muscles including gastrointestinal smooth muscles [1, 12,13,14, 22]. Therefore, we investigated the effects of selective PDE inhibitors for PDE1-5, 7 or 9 on CCh-induced contractions of the smooth muscles in the bovine abomasum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PDE1 enzymes have been reported to be involved in heterogeneous functions such as smooth muscle cell proliferation (PDE1C [5]), Cl – secretion by human colonic epithelial cells [9], interleukin (IL)‐13 production by CD3/CD28‐stimulated human T‐lymphocytes [10], the acrosome reaction of human spermatozoa [11], lipopolysaccharide‐induced IL‐6 release from alveolar epithelial cells [12], glucose‐induced insulin secretion from insulinoma cells [8], contraction of ureteral smooth muscle cells [13], hypoxic pulmonary remodeling [14], granulocyte–macrophage colony‐stimulating factor‐induced human monocyte‐to‐macrophage differentiation (PDE1B [15]), and gall bladder relaxation [16].…”
mentioning
confidence: 99%